Determination of Gastrointestinal Toxicity of Selective COX-2 Inhibitors in Comparison with Conventional NSAIDs - K. Hima Bindu; G. Venkat Rao (Current Aspects in Pharmaceutical Research and Development Vol. 6, 2021)
Background: Adverse gastrointestinal events are the commonest unwanted effects of the NSAIDs, and are believed to result mainly from the inhibition of gastric COX-1, which is responsible for the synthesis of prostaglandins that normally inhibit acid secretion and protect the mucosa. Previous studies report, that selective COX-2 inhibitors are safer when compared to non-selective cyclooxygenase inhibitors, regarding their adverse effects on gastrointestinal system. But, recent studies reveal, that gastrointestinal safety of these selective COX-2 inhibitors is not much better than that of conventional NSAIDs. Aims: In view of the wider usage of selective COX-2 inhibitors, the study has been taken up to report, whether selective COX-2 inhibitors have got any advantages over conventional NSAIDs or not, in regard to their gastrointestinal side effects. Methods: Patients were divided into eight groups, fifteen patients of each. Each group was given one of the NSAIDs from the eight drugs those were selected for the study, for 15 days. In the selected group, along with the symptomatic assessment of gastric toxicity, both pre and post-treatment values of Hb% are estimated, tabulated & subjected to statistical analysis. Results: Both the drugs; diclofenac & meloxicam have shown significant changes in the Hb% values (‘p’ value 0.02 each), whereas selective COX-2 inhibitors like nimesulide & celecoxib were no less in gastric toxicity, in comparison with diclofenac; on symptomatic assessment. Diclofenac and meloxicam have shown significant change in the ‘p’ value, in the assessment of Hb% change both before and after treatment, showing that there must have been gastric bleeding erosions which must have given rise to such changes and thus to anemia, without any alarming symptoms. Conclusions: In our short-term study, selective COX-2 inhibitors did not show any advantage over non-selective NSAIDs regarding their gastrointestinal toxicity.